Pendidikan Politik sebagai Bagian dari Hak Politik Warga Negara - Jatnika, Windan (AHKAM, 2022)
Human Rights (HAM) is a set of rights that humans naturally get since they are born, therefore these human rights must be protected. The development of Human Rights is influenced by several thoughts that gave birth to theories and concepts of Human Rights (HAM). The view of Human Rights (HAM) is based on the idea that human rights are a social phenomenon formed by humans, the result of which is the human rights law. The presence of the state through law is the embodiment of the concept of Human Rights which aims to order human life. This study describes political education as one of the human rights that must be protected by the state. Political education is important, especially in dealing with elections in order to produce democratic elections. The results of this study found that the political education obtained by the community is still low, the role of political parties in carrying out the function of political education to the community is also not optimal and tends to be pragmatic.